Spiritual Education - Muhammad Sofwan; Zulfahmi Lubis; Ilham Rahmat; Ilham Putra Pratama; Nazri Adlani Harahap (Jurnal Multidisiplin Sahombu, 2024)
Education is a part of human life that is very seriously considered, because with this education humans are protected from ignorance in understanding life and distinguishing it from animals, because humans and animals are creatures of God which are only separated by reason because each other has elements that are at least divided into two parts, namely physical and spiritual, researchers often discuss how to care for the physical and sometimes the spiritual is rarely discussed in more depth. In fact, the spiritual must also be taught and educated with a foundation that comes from the Prophet Muhammad SAW.